CITED2 Binding to EP300 Regulates Human Spermatogonial Stem Cell Proliferation and Survival Through HSPA6 - Yongzhe Chen; Bang Liu; Sisi Tao; Lvjun Liu; Jianxin Gao; Ying Liang; Weilei Dong; Dai Zhou (Stem Cells International)
Spermatogonial stem cells (SSCs) are essential for the initiation and continuation of spermatogenesis, a process fundamental to male fertility. Despite extensive studies on mouse SSCs, the mechanisms governing self-renewal and differentiation in human SSCs remain to be elucidated. This study investigated the regulatory mechanisms of SSCs by analyzing single-cell sequencing data from the GEO dataset of human testis. Analysis revealed dominant expression of CITED2 in human SSCs. Reduction of CITED2 levels in hSSC lines significantly inhibited proliferation and increased apoptosis. Protein interaction prediction and immunoprecipitation identified interactions between CITED2 and EP300 in SSC lines. RNA sequencing results indicated that CITED2 knockdown significantly affected the MAPK pathway and the HSPA6 gene. Overexpression of HSPA6 mitigated the proliferative and apoptotic changes provoked by CITED2 downregulation. These findings provide novel insights into the regulatory and functional mechanisms of CITED2-mediated hSSC development.